Perancangan Sistem Manajemen Mutu ISO 9001:2015 pada PT Alam Jaya Seafood - Reynaldo Nyoto Widjojo; Jani Rahardjo (Jurnal Titra, 2020)
The research is conducted to plan the Quality Management System of PT Alam Jaya Seafood. PT Alam Jaya Seafood must assure the quality in the form of ISO 9001:2015 certification. After doing the initial gap analysis, the percentage of initial clause fulfillment is 60,31% and the completeness of document is 48,02%. All deficiencies must be met to obtain ISO 9001:2015 certification. PDCA Method is used in planning QMS ISO 9001:2015 design. Initial gap analysis is conducted in the beginning and the end of the research. Besides, the FMEA Method is used to conduct the risk on the company. As the result of this study, it is found that the percentage of clause fulfillment increases to 90,00% and document fullfilment increases to 80,35%.